Analisis Pengaruh Kepemimpinan, Lingkungan, Motivasi, Dan Kemampuan Kerja Terhadap Kinerja Karyawan - Rumengan, Yani Handri (Universitas Sam Ratulangi, 2013)
This study aims to analyze several variables that can affect the performance of employees: leadership, work environment, work motivation and ability to work. Whether these variables simultaneously and partially affect employee performance. Hypothesis proposed in this study are as follows: (1) alleged leadership, work environment, work motivation and ability to work simultaneously affect the performance of employees. (2) thought leadership, work environment, work motivation and ability to work in a partial effect on employee performance. The population in this study were all employees at PT. Pertani (Persero) Marketing Area Sulawesi number of 62 people. This study used multiple linear regression analysis model. Conclusions of this research are as follows: (1) the factors of leadership, work environment, work motivation and ability to work simultaneously affect the performance of the employees of PT. Pertani (Persero) Marketing Area Sulawesi, four factors contribute to employee performance by 69.2% and the remaining 30.8% was contributed by other variables outside the 4 independent variables studied. (2) Leadership factors, work environment, motivation and ability to work partially affect the performance of the employees of PT. Pertani (Persero) Marketing Area Sulawesi. Keywords: leadership, work environment, performance